2017
DOI: 10.22235/cp.v11i2.1349
|View full text |Cite
|
Sign up to set email alerts
|

Expectativas Académicas Y Habilidades Sociales en La Adaptación a La Universidad

Abstract: Este estudo teve como objetivo relacionar as habilidades sociais (HS), expectativas acadêmicas e adaptação à Universidade, para verifi car o impacto das variáveis HS e expectativas acadêmicas na adaptação à universidade. Participaram 177 estudantes de instituições públicas e privadas de vários cursos e períodos, com idades variando de 17 a 44 anos sendo que 71.2% eram mulheres. Foram usados como instrumentos o Inventário de Habilidades Sociais (IHS), Questionário de Expectativas Acadêmicas (QEA) e o Questionár… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
2
0
3
Order By: Relevance
“…Sin ce social skills are basic elements for interpersonal relationships (Del Prette & Del Prette, 2001a) and relationship problems (Castro & Teixeira, 2013;Pascua-Cantarero, 2016) and social integration diffi culties (Pascua-Cantarero, 2016) may aggravate dissatisfaction with the college experience and lead to increased student drop-out, it is believed that the participants in this study who exhibited a good, below-the-median and a defi cient repertoire of social skills might possibly be indicated for Social Skills Training (THS) programs, once their specifi c defi cits have been assessed. THS has been documented as an eff ective alternative for the interpersonal development of college students (Lima & Soares, 2015;Lopes, Dascanio, Ferreira, Del Prette, & Del Prette, 2017) and so it could reduce dropout rates in higher education, since a wellprepared repertoire of social skills can facilitate college students' adaptation to higher education (Soares, Francischetto, Peçanha, Miranda, & Dutra, 2013;Soares et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sin ce social skills are basic elements for interpersonal relationships (Del Prette & Del Prette, 2001a) and relationship problems (Castro & Teixeira, 2013;Pascua-Cantarero, 2016) and social integration diffi culties (Pascua-Cantarero, 2016) may aggravate dissatisfaction with the college experience and lead to increased student drop-out, it is believed that the participants in this study who exhibited a good, below-the-median and a defi cient repertoire of social skills might possibly be indicated for Social Skills Training (THS) programs, once their specifi c defi cits have been assessed. THS has been documented as an eff ective alternative for the interpersonal development of college students (Lima & Soares, 2015;Lopes, Dascanio, Ferreira, Del Prette, & Del Prette, 2017) and so it could reduce dropout rates in higher education, since a wellprepared repertoire of social skills can facilitate college students' adaptation to higher education (Soares, Francischetto, Peçanha, Miranda, & Dutra, 2013;Soares et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between social skills and the student's academic adaptation has been investigated in various studies. A recent study by Soares, Santos, Andrade, and Souza (2017) investigated the relationships that exist between social skills, academic expectations and adaptation to college in personal, interpersonal, vocational and institutional terms, and aspects referring to study skills (time management, for example), using a sample of 177 male and female college students, aged 17-44, from public and private institutions in the State of Rio de Janeiro. The results indicated that college students who had a better-prepared repertoire of social skills and realistic expectations about achieving their academic and professional goals within the college context adapted better to higher education.…”
Section: Asociación Entre Habilidades Sociales Factores Sociodemográmentioning
confidence: 99%
“…La confiabilidad y validez: es de 0,74 y presenta una confiabilidad de 0.88 Gil (19). La escala se puede interpretar con un bajo nivel de habilidades sociales tiene un puntaje de 25 o menos, el nivel medio de las habilidades sociales presenta un puntaje de entre 26 y 74 y el nivel alto de habilidades sociales comprende una puntuación de 75 o más (20).…”
Section: Instrumentosunclassified
“…Incidencia de género y rama de conocimiento sobre expectativas académicas del alumnado de nuevo ingreso Incidence of gender and branch of knowledge on academic expectations of fi rst-year students condicionar su adaptación universitaria (Benevides Soares, de Almeida Santos, de Andrade y Siqueira de Souza, 2017;Braxton, Vesper y Hossler, 1995;Marinho-Araújo, Fleith, Almeida, Bisinoto y Rabelo, 2015). Asimismo, Casanova, Almeida, Peixoto, Ribeiro y Marôco (2019) afi rman que, cuando las expectativas iniciales de los estudiantes son demasiado altas o poco realistas, es más probable que no las cumplan.…”
unclassified